METHODOLOGY OF LEARNING THE RUSSIAN LANGUAGE IN HIGHER EDUCATION - Muslimova Rano Muratovna (American Journals, 2023)
This scientific article explores the methodology of learning the Russian language in higher education institutions. The study focuses on the effective approaches and strategies employed to facilitate language acquisition, proficiency, and cultural understanding. The article presents a comprehensive approach that includes communicative strategies, proficiency-based instruction, integrated skills development, task-based learning, language immersion, technology-enhanced learning, and cultural integration. The findings emphasize the significance of a multifaceted methodology in equipping students with the necessary language skills and cultural competence for successful language learning in higher education.
Keywords: Methodology, Russian language, higher education, language acquisition, proficiency-based instruction, integrated skills development, task-based learning, language immersion, technology-enhanced learning, cultural integration.